Mapeamento das estratégias utilizadas nos processos de distribuição e homenagem em uma distribuidora de hortifrutigranjeiro na região de Araguaína-TO - Farias, Denyse Fernandes (Universidade Federal do Tocantins, 2020)
This article aims to observe and analyze the strategies used in the process of distribution and warehousing of a distributor in the region Horticultural. Araguaína-TO. For this, we used a theoretical approach addressing issues related to the sector Horticultural.as a whole, and so specific aspects related to the supply chain, quality, seasonality, storage and distribution grocers. The methodology used was descriptive research, using the procedure of the methodological case study with qualitative approach. As an instrument for data collection was used the interview and application questionnaire with open questions to the director of that distributor. The results of the case study on a distributor in the industry to Horticultural. post-harvest Araguaína- TO indicate that the strategies used in the organization are effective and some are yet to be developed to allow the distributor to decrease problems with spoiled food and avoid costs in entry and exit of goods.